Analyses of Space Vector PWM Inverter Under Fault Conditions - Ammar Sami Mohammed; Majid K. Al-Khatat (Engineering and Technology Journal, 2013)
The Space-Vector Pulse Width Modulation (SVPWM) technique has become a popular pulse width modulation technique. In this paper, performance investigation of space vector PWM inverter feeding three phase R-L load under fault conditions are presented.The common faults occurred in the power switches of Space Vector PWM bridge inverter, such as; open transistor and misfiring transistor. These faults are implemented, built to get experimental and simulation results. The time and frequency domain analyze has been used to compare and analyze different fault cases with the normal operation in SVPWM inverter.The obtained results show that the model is accurate, applicable and gives a good identification, information and diagnostic rules for the different faults.